Structural Investigations on Co(II), Ni(II) and Cu(II) Biligand Coordination Compounds with 7-Hydroxy-4-Phenyl-6-(α-Naphthyl)-Aminomethyl Coumarin as Primary and 4-Nitroso-1-Hydroxy-2-Naphthoic Acid As Secondary Ligand - K. Agarwal, Suresh; Lal, Manohar (Asian Journal of Chemistry, 2010)
Biligand coordination compounds of Co(II), Ni(II) and Cu(II),with 7-hydroxy-4-phenyl-6-(α-naphthyl)-aminomethyl coumarin(L' H) as primary and 4-nitroso-1-hydroxy-2-naphthoic acid (L" H)as secondary ligand have been synthesised. Analytical data suggested1 : 1 : 1 (M : L' H : L" H) stoichiometric composition for theisolated compounds. The conductance data (3.8-4.7 ohm-1cm2/mol-1) in DMF at the concentration 10-3 M indicate nonelectrolyticbehaviour of the coordination compounds. Magnetic andspectral studies show that the Cu(II) complex is square-planar whileNi(lI) and Co(ll) complexes are octahedral. TG studies show thepresence of two moles of coordinated water in Ni(lI) and Co(ll)complexes.